Designing and managing programs an effectiveness-based approach - Kettner, Peter M.; Moroney, Robert M.; Martin, Lawrence L. (Thousand Oaks, California Sage Publications, 2023)
"This classic text for social work and human services helps readers grasp the meaning and significance of measuring performance and evaluating outcomes. Hands-on and practical, Designing and Managing Programs incorporates the principles of effectiveness-based planning as it addresses the steps of designing, implementing, and evaluating a human services program at the local agency level. Written by leaders in the field, it guides students through the process from beginning to end. Meaningful examples--from problem analysis and needs assessment to evaluating effectiveness and calculating costs--enhance reader understanding of how concepts are implemented in the real world. The Sixth Edition contains new examples and references, and updates based on changes to federal regulations"
Keywords: Social service -- United States -- Planning; Social service -- United States -- Evaluation; Social service -- United States -- Finance